Candy‐striped spider leaf and habitat preferences for egg deposition. (27th April 2022) - Cuff, Jordan P.; Evans, Sharon Aifionn; Porteous, Ian Angel; Quiñonez, Julia; Evans, Darren M.
Abstract: Candy‐striped spiders ( Enoplognatha spp.; Araneae: Theridiidae) are among Britain's commonest theridiid spiders and are potential immigrant biocontrol agents of many pests in arable fields. Though the presence of these spiders in proximity to agriculture is dependent on the availability of suitable leaves for their egg deposition, their preference for different plant species and habitat types has not been fully investigated. Candy‐striped spiders were observed in leaf‐rolls during transect surveys of semi‐natural habitats (hedgerow, woodland and grassland) adjacent to oilseed rape fields at 10 sites across northeast England in August and September 2021. The local plant community was surveyed and compared against the leaves used by candy‐striped spiders via null models. Candy‐striped spiders preferentially deposited their eggs in hedgerow, demonstrating relative avoidance of woodland and grassland. They exhibited preference for bramble, common nettle and hogweed leaves, but also used those of dock, ash and blackthorn. Candy‐striped spiders appeared to preferentially use leaves with roughly equal length and width and avoided longer, narrower leaves irrespective of their total size. The leaves used by candy‐striped spiders are taxonomically broad, but share some morphological commonalities. Candy‐striped spiders exhibit some degree of generalism, regularly utilizing suboptimal leaves in sites lacking their preferences. The availability of preferred plants for these spiders in agriculturally proximate semi‐natural habitat may enhance their possible contribution to biocontrol. Abstract :